Photopenic Lesions in Bone Marrow Scintigraphy Using Technetium-99m Labeled Antigranulocyte Antibody without Known Tumour - Krause, Th.; Reinhardt, M.; Nitzsche, E.; Moser, E. (Nuklearmedizin - NuclearMedicine, 1999)
Aim: The purpose of this study was to elucidate the frequency of photopenic lesions in patients without known tumour disease by using bone marrow scintigraphy with Tc-99m labeled anti-NCA-95. Methods: Whole body immunoscintigraphy (IS) was performed in 141 consecutive patients with fever of unknown origin. The age ranged between 20 and 88 years with a mean age of 57 years. None of the patients had known tumour disease. Scans were evaluated with respect to photopenic lesions and to bone marrow distribution. Results: IS showed bone marrow defects in the axial skeleton in 16 patients (11 %). With the help of the typical scintigraphic defect pattern, the cause of the lesions was clearly identified as degenerative changes in four patients and in one patient as due to prior sternotomy. In the remaining 11 patients the origin of the defects became evident when the case history or additional imaging was consulted. The mean age of these 16 patients was 69 years ranging from 50 to 88 years. There was an age-related frequency of defects. 10% of the patients from 50 to 59 years showed defects, 60-69 years 9%, 70-79 years 30%, and 33% of the patients from 80 to 89 years had defects. IS was not hampered by tracer uptake to liver or spleen in 93 patients. Left caudal ribs were obscured in 48 patients with intense tracer uptake to the spleen. No or markedly reduced tracer uptake was found in caput humeri and caput femori in 94 and 82 patients, respectively. Patchy tracer uptake to the bone marrow of the limbs was seen in 13/62 patients showing marrow expansion in the lower limbs and 14/55 with marrow expansion in the upper limbs. The patchy pattern was asymmetric in 12 of these patients. Conclusion: The results of the present study reveal that using Tc-99m NCA-95, photopenic lesions of the bone marrow are rarely seen in patients without known malignant disease. The occurrence of benign lesions is age-related. The benign cause of the lesion was obvious from location and pattern of the lesion in about 30% of the cases. Evaluation of lesions in the upper and lower limbs may be hindered due to physiological variation of marrow distribution. Nevertheless, IS appears to be well-suited for the detection and localization of bone marrow metastases.
Keywords: Tc-99m NCA-95; bone marrow scintigraphy; immunoscintigraphy; bone marrow lesion